MODEL PEMBELAJARAN BLENDED-CYBER: INOVASI PROBLEM SOLVING DALAM PENGAJARAN, PENELITIAN, SUMBER BELAJAR, DAN PERANAN ETIKA SETELAH PASCA COVID-19 - Harianto GP (Sekolah Tinggi Teologi Excelsius, 2021)
Abstract: The rapid development of technology that goes beyond human thought has now entered the Industrial Revolution 5.0: a metaverse life (a world of unlimited virtual communication) driven by the power of the internet, digitization, computers, and the like. Blended learning has become indispensable in the development of learning strategies in educational institutions even after Covid19. This study elaborates on the meaning, structure, and types of blended-cyber learning as a problem-solving innovation in teaching, research, learning resources, and the application of ethics in post-secondary education. Literature Review with the results: (1) Cyber Blended Learning is an online learning environment that focuses on students to facilitate learning activities via the Internet. The online learning environment is not only a website as a place to transfer paper materials into electronic files, but can also use e-mail. e-mail or other electronic means. The blended-cyber learning model always requires different work tools depending on the needs of each educational institution, therefore Blended Cyber is designed according to the needs of the objectives of the teaching and learning process. (2) Blended CyberLearning is the right and relevant solution to solve various cases of learning processes and resources. It is basically a combination of the benefits of learning that occurs in person and virtually. BlendedCyber Learning Model: (a) Innovation in problem-solving in teaching as a designer of various BlendedCyber Learning models. (b) Innovation in solving research problems by placing learning resources, latest research, and publications in various journals around the world (c) Innovation in solving problems in very effective learning resources. (d) Problem-Solving Innovation in solving ethical problems in the use of learning resources. It is recommended to adjust the use of the blended-Cyber learning model with the objectives of each teaching and learning process of educators.Abstrak: Perkembangan teknologi yang pesat yang melampaui pemikiran manusia kini memasuki Revolusi Industri 5.0: kehidupan metaverse (dunia komunikasi virtual tanpa batas) yang didorong oleh kekuatan internet, digitalisasi, komputer dan sejenisnya. Pembelajaran Blended telah menjadi sangat diperlukan dalam pengembangan strategi pembelajaran di lembaga pendidikan bahkan setelah Covid19. Kajian ini mengelaborasi pengertian, struktur dan jenis-jenis pembelajaran blended-cyber dan sebagai inovasi pemecahan masalah dalam pengajaran, penelitian, sumber belajar dan penerapan etika pasca pendidikan menengah. Tinjauan Pustaka dengan hasil: (1) Pembelajaran Blended Cyber adalah lingkungan belajar online yang berfokus pada siswa untuk memfasilitasi kegiatan belajar melalui Internet.Lingkungan belajar online tidak hanya berupa website sebagai tempat untuk mentransfer bahan kertas ke dalam file elektronik, tetapi juga dapat menggunakan e-mail atau sarana elektronik lainnya. Model pembelajaran blended-cyber selalu membutuhkan perangkat kerja yang berbeda-beda tergantung kebutuhan masing-masing institusi pendidikan, oleh karena itu Blended Cyber dirancang sesuai dengan kebutuhan tujuan dari proses belajar mengajar. (2) Pembelajaran Blended Cyber adalah solusi yang tepat dan relevan untuk menyelesaikan berbagai kasus proses dan sumber belajar. Ini pada dasarnya merupakan kombinasi dari manfaat pembelajaran yang terjadi secara langsung dan virtual. Model Pembelajaran BlendedCyber: (a) Inovasi dalam pemecahan masalah dalam pengajaran sebagai perancang berbagai model Pembelajaran BlendedCyber.(b) Inovasi dalam memecahkan masalah penelitian dengan menempatkan sumber belajar, penelitian terbaru dan publikasi di berbagai jurnal di seluruh dunia (c) Inovasi dalam memecahkan masalah dalam sumber belajar sangat efektif. (d) Problem Solving Inovasi dalam memecahkan masalah etika dalam penggunaan sumber belajar. Disarankan untuk menyesuaikan penggunaan model pembelajaran blended-Cyber dengan tujuan dari setiap proses belajar mengajar pendidik.Kata kunci: model pembelajaran Blended-Cyber; problem solving, pengajaran, penelitian, sumber belajar; etika